Multimodal Repair of Osteoporotic Fractures With an Exosome‐ECM Integrated Hydrogel - Ziheng Wei; Fen Tang; Wenda Xu; Yongzhi Cui; Songyan Gao; Qingjie Kong; Si Chen; Xiongsheng Chen (Advanced Healthcare Materials, 2026)
ABSTRACT Osteoporotic fractures pose a significant clinical challenge in aging societies due to the limited efficacy and high re‐fracture risk associated with conventional treatments. To address this, we developed EXOs@ECM‐SCS, a multifunctional bioactive hydrogel that encapsulates exosomes derived from induced pluripotent stem cell‐induced mesenchymal stem cells within a hybrid matrix of decellularized extracellular matrix and methacrylated sulfated chitosan. This composite system promotes bone regeneration through a synergistic strategy that concurrently targets angiogenesis, immunomodulation, neurogenesis, and osteogenesis (AINO). Experimental results demonstrated that EXOs@ECM‐SCS significantly enhanced osteogenic differentiation, angiogenic activity, and neural regeneration, while also driving macrophage polarization toward the M2 phenotype. These multifaceted effects collectively improved bone mass accumulation, mineralization, and fracture healing in an osteoporotic mouse model. Mechanistic insights from exosomal sequencing highlighted the involvement of key miRNAs such as miR‐100‐5p and miR‐320a‐3p, along with PI3K‐Akt and MAPK signaling pathways. These findings underscore EXOs@ECM‐SCS as an innovative therapeutic platform that leverages coordinated multimodal regulation to accelerate osteoporotic fracture repair.